Peran Badan Permusyawaratan Desa (BPD) dalam Penyelenggaraan Program Pemerintahan di Desa Bualemo Kecamatan Kwandang Kabupaten Gorontalo Utara - Pano, Sahrin S.; Gobel, Lisda Van; Nggilu, Rukiah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
The background of the research examines the importance of the role of the Village Consultative Body (BPD) based on the duties and functions of the Village Consultative Body (BPD) in the Village Government Program. The purpose of this research is to understand the role of the Village Consultative Body (BPD) in the implementation of government programs in Bualemo Village, Kwandang District, North Gorontalo Regency. The research method used is qualitative with a descriptive type of research. The research results show that the coordination of the Village Consultative Body (BPD) is not yet optimal, as evidenced by the lack of information transparency and coordination that is not fully proactive. The cooperation between the Village Consultative Body (BPD) and the Village Government has not been fully effective, as evidenced by the lack of attendance of BPD members at the office, which delays decision-making by the Village Government and results in minimal meetings with the Village Government. The evaluation of the Village Consultative Body (BPD) is still lacking in the implementation of government programs. Although the Village Consultative Body (BPD) participates in discussions and provides opinions, the implementation of evaluations is still limited and often not well-documented.